Bounds on g(5)1(v) for v = 9,13,17 (mod 20) - Grannell M.J.; Griggs T.S.; Stanton R.G. (Utilitas Mathematica, 2009)
The minimum number of blocks having maximum size precisely five that is required to cover, exactly once, all pairs of elements from a set of cardinality v is denoted by g1(5) (v). The exact values of g 1(5) (v) for v = 20t + r are known for r ε {0, 1, 2, 3, 4, 5, 18, 19}. In this paper, we study the cases r = 9, 13, 17.